Failure and prospect Lazarus and the rich man (Luke 16:19-31) in the context of Luke-Acts - Bredenhof, Reuben (London, England Bloomsbury Publishing, 2018)
"Bredenhof analyses the parable of Lazarus and the Rich Man (Luke 16:19-31) by examining its functions as a narrative, considering its persuasiveness as a rhetorical unit, and situating it within a Graeco-Roman and Jewish intertextual conversation on the themes of wealth and poverty, and authoritative revelation. The parable portrays the consequences of the rich man's failure to respond to the suffering of Lazarus. Bredenhof argues that the parable offers its audience a prospect for alternative outcomes, in response both to poverty and to a person who has risen from the dead. This prospect is particularly evident when the parable is read in anticipation of the ethical and theological concerns of Luke's second volume in Acts. Bredenhof asserts that reading within the context of Luke-Acts contributes to the understanding of Luke's purposes with this narrative. It is in Acts that his audience witnesses the parable's message about mercy being applied through charitable initiatives in the community of believers, while the Acts accounts of preaching and teaching demonstrate that a true reading of "Moses and the prophets" is inseparably joined to the believing acceptance of one risen from the dead. Through a re-reading of Luke 16:19-31 in its Luke-Acts context, its message is amplified and commended to the parable's audience for their response."--
Acknowledgments Chapter 1 - The Continuing Study of Luke 16:19-31 Chapter 2 - Luke 16:19-31 as Narrative Chapter 3 - Rhetoric in Luke 16:19-31 Chapter 4 - Intertextuality in Luke 16:19-31 Chapter 5 - Luke 16:19-31 within Luke-Acts Chapter 6 - Conclusions and Implications Bibliography Index
Includes bibliographical references (pages 212-234) and indexes
Restricted to subscribers or individual electronic text purchasers
Revision of author's thesis (Ph. D.)--St Mary's University, Twickenham, London, 2016
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Lazarus -- Saint (Poor man from the Gospel of Luke); Lazarus - Saint (Poor man from the Gospel of Luke); Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Rich man and Lazarus (Parable) -- Criticism, interpretation, etc; Lazarus; Bible; Rich man and Lazarus (Parable); Criticism, interpretation, etc; Hochschulschrift